(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article treats about efficiency ofthe public expenses in Poland on the back-ground of the EU-27. It shows the comparing surfaces which are the basis on rating propriety of public finance administration in Poland in relation to extant European Un-ion countries. Guided analysis showing an areas which exacting of changes and conse-quences of forsaken reforms. The article proclaim the empirical view on efficiency and rationality of public sector administration.